Updated analysis of irritable bowel syndrome: a review of the literature - Coronel, Martin (2020)
Irritable bowel syndrome (IBS) is a chronic pathology with disorders of the bowel-brain interaction, characterized by abdominal pain localized anywhere in the abdomen as well as bowel habit alteration (constipation, diarrhea or mixed), in the absence of any disease that can cause these symptoms. With the updated concepts according to the latest meeting of experts in Rome 2016, our goal is to raise awareness about irritable bowel syndrome, by reviewing the literature regarding definition, classification, pathophysiology, clinical aspects, treatment, prognosis and the future. IBS is a chronic pathology, characterized by abdominal pain, at least 1 day per week in the last 3 months, associated with the alteration of the intestinal bowel habits.With a classification based on the alteration of intestinal bowel movements and in addition to constipation induced by opioids or narcotics, the etiology and pathophysiology are not well explained or well-known so far. The clinical aspects are based on the Rome IV criteria. A good doctor-patient relationship is key to reassuring the patient’s doubts about his illness, which increases the chances of adherence to individualized treatment from patient to patient depending on the sing and symptoms that may manifest in those that include: dietary advice, psychological support, in some cases pharmacological prescription, suspension of medications or change medications, minimize the dose of drugs or suspend, according to the needs of the patient as is the case of opioids. The prognosis is still uncertain, and a promising future to illustrate new definitions, classifications, pathophysiologies, clinical aspects and treatments according to the type of clinical  anifestation of each patient.